Security for Multi-hop Wireless Networks - Mahmoud, Mohamed M. E. A.; Shen, Xuemin (Sherman) (SpringerBriefs in Computer Science, 2014)
This Springer Brief discusses efficient security protocols and schemes for multi-hop wireless networks. It presents an overview of security requirements for these networks, explores challenges in securing networks and presents system models. The authors introduce mechanisms to reduce the overhead and identify malicious nodes that drop packets intentionally. Also included is a new, efficient cooperation incentive scheme to stimulate the selfish nodes to relay information packets and enforce fairness. Many examples are provided, along with predictions for future directions of the field. Security for Multi-hop Wireless Networks demonstrates recent research that enhances the efficiency and safety of these key networks. Concise and practical, it is a useful tool for researchers and professionals working in network security. It is also a valuable resource for advanced-level students interested in wireless communications and networking.